Lecturer’s Voice of Teaching Speaking through Zoom Meeting Platform Narrative Study in Banjarmasin - Umar, Vebrianti (General English Education, 2025)
Speaking is one of English skill that supports the communication in class : the lecturer must be able to convey and explain material to the student, the student also should be active in sharing ideas, information and positive argumentation. In this digital era, lecturer build student’ speaking skill flexibility by conducting online teaching process. One of the online platforms for teaching the skill is zoom meeting. It offers some features that facilitate online communication between lecturer and student: synchronous audio and video conferencing. In the teaching process using zoom meeting, the lecturer undoubtedly experience and faces various situations. Therefore, this qualitative research, which emphasizes a narative design, researcher investigate  the lecturer experiences  through observation and interview. Moreover, all the research activity were carefully and systematically documented.  The final stage is data analysis using a coding system and interpret the analyzed data to derive meaningful research outcomes.This research proved the features of the zoom meeting  : share screen, white board and breakout room  support the teaching and learning of speaking..  However, the lecturer  also find a connection problem It means that the use of zoom meeting in the class should be equipped by the good internet connection.